The Effectiveness of Missouri Mathematics Project Learning Models for Improving Students’ Mathematical Connection Ability on Junior High School - Apriani, Dini; Putra, Harry Dwi; Hendriana, Heris (IKIP Siliwangi, 2024)
Mathematical connection ability is one of the high level abilities but is still classified as low because students' understanding of the conceptual material given by the teacher, there are still students going through steps in working on the problems given, such as describing a symbol, in completing mathematical concepts, therefore This research aims to examine the effectiveness of using the Missouri Mathematics Project Learning Model carried out at MTs Ibnu Sina Jl. Tegal Overtime No. 105, Pamekaran, District. Soreang, Bandung Regency, West Java 4091, by taking a sample of 60 students consisting of control and experimental classes. The research method used in this action was the experimental method. Based on the results of descriptive analysis of students' mathematical ability data before being given treatment, it showed the highest score was 70, the lowest score was 55 and the average score was 61. Meanwhile, the results of descriptive analysis of students' mathematical ability data after being given The treatment showed the highest score of 70, the lowest score of 55 and the average score of 61. Those given the treatment showed the highest score of 87, the lowest score of 69, and the average score of 77.83. So the average mathematical connection ability of students after being given treatment is higher than the students' mathematical ability before being given treatment.